1)-3,9*2,8=-10,92
2)-10,92+26,6=15,68
3)15,68:(-3,2)=-4,9
4)-4,9-2,1=-7
Сначала упростив второе выражение.
отсюда 39a-15b+25=(39a-15b+24)+1=0+1=1
Упростить=перести в обыкновенную
0.60 = 3/5
3.400 = 3 2/5
5.020 = 5 1/50
14.5000 = 14 1/2
100.1010 = 100 101/1000
5.0100 = 5 1/100
7 (x-19)=133
7x-133=133
7x=133+133
7x=266
x=266/7
x=38
9 (213-2x)=927
1917-18x=927
18x=1917-927
18x=990
x=990÷18
x=55
1344÷(x+26)=32
x+26=1344÷32
x+26=42
x=42-26
x=16
384÷(51-5x)=24
51-5x=384÷24
51-5x=16
5x=51-16=35
x=35÷5=7